Małżeństwa w Polsce współczesnej. Studium empiryczne - Dąbrowska, Zofia (Wydawnictwo Naukowe UAM, 2001)
The study is based on the results of Polish gamological investigations, mainly from the 1990s. The author describes various features and determinants of modern marriages in Poland. They are characterized, among others, by selection of spouses according to demographic-social and regional factors, determination of marital success (various types), the problem of sexual satisfaction in marriage, the effect of religious attitudes of spouses on the duration of their union, the problem of violence in marriage (including sexual violence), and also the problem of health and wellbeing of spouses in older age. The author discusses also the specific problems of semarriagese, that is reconstructed families, especially their legal and psychological problems.
Marriages in modern Poland. Empirical study